Reinforced concrete deep beams with web openings - Sharp, Graham Richard (1977)
The design of reinforced concrete deep beams is not yet covered by the current British Code CP110: 1972. Some provisions are given in the CEB-FIP Recommendations (1970) and the AC1318-71 Building Code, and the new (1977) CIRIA design guide contains more comprehensive guidance including a number of recommendations for the design of deep beams with web openings.